2010
DOI: 10.1016/j.tox.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal peroxisome proliferator-activated receptor α (PPARα) agonism on postnatal development

Abstract: Recent work indicates that PPARalpha is required for perfluorooctanoic acid (PFOA)-induced postnatal lethality resulting from prenatal exposure. The present study tested the hypothesis that relatively modest activation of PPARalpha during prenatal development will cause postnatal lethality, similar to that observed with PFOA, a relatively low affinity PPARalpha agonist. Female wild-type and Pparalpha-null mice were mated overnight with males of the same genotype. The presence of a copulatory plug on the mornin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Studies with knock-out mice showed that postnatal mortality in mouse could be mediated via mouse PPARα but not via a humanized form of the receptor, suggesting species differences in response to receptor binding [ 38 , 39 ]. However, modest activation of PPARα during prenatal development using the agonists clofibrate and Wy14,643 caused no postnatal mortality in mouse [ 40 ]. In chicken, cardiac effects induced by embryonic PFOA exposure could partly be reproduced by the PPARα agonist Wy 14,643 [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies with knock-out mice showed that postnatal mortality in mouse could be mediated via mouse PPARα but not via a humanized form of the receptor, suggesting species differences in response to receptor binding [ 38 , 39 ]. However, modest activation of PPARα during prenatal development using the agonists clofibrate and Wy14,643 caused no postnatal mortality in mouse [ 40 ]. In chicken, cardiac effects induced by embryonic PFOA exposure could partly be reproduced by the PPARα agonist Wy 14,643 [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of pregnant mice to etofylline clofibrate or fenofibrate from GD7 to 16 at high dosages resulted in FGR (etofylline clofibrate) and higher postimplantation loss (fenofibrate) (Ujhazy et al, 1989). Palkar et al (2010) saw no increase in neonatal mortality in offspring of mice fed diets containing clofibrate or WY-14643 during pregnancy, in contrast to their subsequent findings with PFOA (Albrecht et al, 2013). The authors suggested that the lack of neonatal mortality from clofibrate or WY-14643 was due to lower activation of PPARα compared with treatments with PFOA that did cause neonatal mortality.…”
Section: Downregulation Of Pparγmentioning
confidence: 99%
“…Já no 21° DL, a redução da massa corporal foi de 19,8% nas mães RC e de 22,7% nas mães RC+GEM (vs. CTL; p<0,01 e p<0,0001).Até o momento, não foram encontrados na literatura trabalhos que correlacionam a exposição da GEM e o peso das ratas prenhas e/ou lactantes. Porém, o estudo de Palkar e colaboradores demonstrou que a administração do clofibrato durante a gestação não afetou o peso ou o ganho de peso das ratas(102). Dessa maneira, observando nossos resultados, a GEM também não foi capaz de alterar o peso das mães que foram expostas à RC.…”
unclassified